2007
DOI: 10.1024/0044-3514.38.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung und Validierung eines Inventars zur Erfassung des Geschlechtsrollen-Selbstkonzepts im Jugendalter

Abstract: Zusammenfassung. In drei Studien wurde ein Instrument zur Erfassung des Geschlechtsrollen-Selbstkonzepts im Jugendalter (GRI-JUG) entwickelt, das positive und negative Attribute enthält. In einer Pilotstudie wurden 40 typische Attribute für Jungen und Mädchen ermittelt. Diese wurden danach von N = 692 Jugendlichen hinsichtlich ihrer Typizität für beide Geschlechter eingeschätzt. Für die Teilskalen Mask+, Mask-, Fem+ und Fem-wurden je fünf Attribute ausgewählt und einer neuen Stichprobe von N = 1926 Jugendliche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…To assess self-perceived femininity and masculinity, positive traits from the Inventory for Measuring Adolescents' Gender Role Self-Concept (GRI-JUG) were used (Krahé et al, 2007). Participants were presented with five masculine attributes (humorous, courageous, sporty, companionable, and strong; α = 0.676) and five feminine attributes (emotional, romantic, industrious, sympathetic, and empathic; α = 0.651) and were asked to rate to what extent each attribute is characteristic of them.…”
Section: Gender Role Self-conceptmentioning
confidence: 99%
“…To assess self-perceived femininity and masculinity, positive traits from the Inventory for Measuring Adolescents' Gender Role Self-Concept (GRI-JUG) were used (Krahé et al, 2007). Participants were presented with five masculine attributes (humorous, courageous, sporty, companionable, and strong; α = 0.676) and five feminine attributes (emotional, romantic, industrious, sympathetic, and empathic; α = 0.651) and were asked to rate to what extent each attribute is characteristic of them.…”
Section: Gender Role Self-conceptmentioning
confidence: 99%
“…2010 ; Krahé et al. 2007 ) und, dass am Gymnasium stärker als an anderen Schulformen selbstregulative Fähigkeiten ausgebildet werden (Artelt et al. 2009 ), lassen sich diese Befunde im Sinne eines adaptiven Unterstützungsverhaltens der Eltern interpretieren.…”
Section: Diskussionunclassified
“…The present research builds on the claim that gender identity comprises both negative and positive aspects that are uniquely related to outcome variables for which gender differences have been identified. In support of this claim, Krahé, Berger, and Möller () developed an instrument to measure gender identity in adolescence that comprised both positive and negative aspects of masculinity and femininity and showed that the positive and negative subscales were associated with distinct psychological constructs. This instrument was tailored to the language usage of adolescents, as reflected in the sampling of typical terms of boys and girls in a pilot study.…”
Section: Conceptualizations Of Gender Identitymentioning
confidence: 99%